2022
DOI: 10.1002/bmc.5441
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms exploration of terrestrosin D on pulmonary fibrosis based on plasma metabolomics and network pharmacology

Abstract: Terrestrosin D (TED) is the active ingredient of Tribulus terrestris L., which is used in traditional Chinese medicine (TCM) formulations and has a wide range of pharmacological activities. A previous study showed that TED alleviated bleomycin (BLM)‐induced pulmonary fibrosis (PF) in mice. However, the mechanisms underlying the therapeutic effect of TED are still unclear and need further investigation. In this study, we evaluated the effect of TED in a mice of BLM‐induced PF in terms of histopathological and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…An in vivo study revealed that the BLM can alter the distribution of metabolites in mice, while terrestrosin D reversed this change by regulating amino acid and lipid metabolism. 15 Baicalin can effectively inhibit the pathological changes of PF caused by BLM. Additionally, baicalin may improve PF by modulating 4 key pathways, including taurine and hypotaurine metabolism, glutathione metabolism, and glycerophospholipid metabolism.…”
Section: Introductionmentioning
confidence: 95%
“…An in vivo study revealed that the BLM can alter the distribution of metabolites in mice, while terrestrosin D reversed this change by regulating amino acid and lipid metabolism. 15 Baicalin can effectively inhibit the pathological changes of PF caused by BLM. Additionally, baicalin may improve PF by modulating 4 key pathways, including taurine and hypotaurine metabolism, glutathione metabolism, and glycerophospholipid metabolism.…”
Section: Introductionmentioning
confidence: 95%
“…Metabolomics investigates the dynamic changes of small molecules in living organisms (Yang et al, 2022). It is often used to reveal the mechanism of action of drugs (X. Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology can elucidate molecular mechanisms of action of metabolomics by finding relationships between compounds and potential targets. Similarly, metabolomics and network pharmacology revealed that terrestrosin D attenuated bleomycin‐induced PF mice, reversed inflammatory damage in the lung by modulating amino acid and lipid metabolism and identified TNF‐ α and TGF‐ β 1 as therapeutic targets 24 . Therefore, metabolomics and network pharmacology analyses are usually combined for the study of metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%